Оптимальна зупинка агрегованих та слабозбурених дезагрегованих марковських та напівмарковських моделей у дискретному часі - Andreev, N. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
An investigated sequential analysis of optimal decision making problems for weakly disturbed Markov and semi-Markov models is based on the sequential solution of optimal stopping problems of nondisturbed aggregate and weakly disturbed dissaggregate models.